The macroeconomic effects of trade policy - Erceg, Christopher J.,Prestipino, Andrea,Raffo, Andrea (Board of Governors of the Federal Reserve System, 2018)
We study the short-run macroeconomic effects of trade policies that are equivalent in a friction-less economy, namely a uniform increase in import tariffs and export subsidies (IX), an increase in value-added taxes accompanied by a payroll tax reduction (VP), and a border adjustment of corporate pro.t taxes (BAT). Using a dynamic New Keynesian open-economy framework, we summarize conditions for exact neutrality and equivalence of these policies. Neutrality requires the real exchange rate to appreciate enough to fully offset the effects of the policies on net exports. We argue that a combination of higher import tariffs and export subsidies is likely to trigger only a partial exchange rate offset and thus boosts net exports and output (with the output stimulus largely due to the subsidies). Under full pass-through of taxes, IX and BAT are equivalent but VP is not. We show that a temporary VP can increase intertemporal prices enough to depress aggregate demand and output, even when wages are sticky. These contractionary effects are especially pronounced under fixed exchange rates
Keywords: Graue Literatur; Trade Policy; Fiscal Policy; Exchange Rates; Fiscal Devaluation